Finding the Social Value of Forests Through Stated Preference Methods: A Mediterranean Forest Valuation Exercise - Riera,Pere (2004)
There are several methods to estimate the social value of forests or forest attributes, the most widely used being the stated preference methods. This paper illustrates the use of such methods to estimate some recreational functions of Mediterranean forests, as well as CO2 sequestration and soil erosion prevention. It also compares the results from a contingent ranking and a choice experiment method application.